(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
When people are aware about financial products and marketthey will be inclined towards financial products which will increase financialinclusion.. Final goal of any financial programme is to empower consumer.Government is aiming for more and more financial inclusion and that can beachieved by educating consumers by financial literacy programmes .Theimportance of financial education has improved in recent years due to thedevelopments in financial markets as well as demographic, economic and policychanges. India is ranked number two in the list of highest financial literacycountries in the world. Moreover booming economy and new horizon of hopes makesthis study really significant. The Reserve bank of India, which is the centralbank, has been actively participating in the field of eradicating financialliteracy in the country. In this context a project called “Project financialliteracy “has already been implemented. Financial literacy in India is on thepositive side now. The survey conducted by The Financial Express shows thatIndia has made rapid progress in the field of financial education among the tenleading nations of the world.